Hereditary hemorrhagic telangiectasia with splenic abscess: a case report - P. Dikshaladevi; N. Selvaratnam; J. Nalayini; T. Peranantharajah (Sri Lanka College of Internal Medicine, 2024)
Hereditary hemorrhagic telangiectasia (HHT) is a rare disorder. Although it commonly causes recurrent bleeding manifestations and severe iron deficiency anaemia, they may be overlooked. Splenic abscess is rarely seen in clinical practice in patients with HHT. This case report describes a patient who presented with epistaxis and severe anaemic symptoms and found to have a splenic abscess with underlying HHT.